Differences in the Effects of "Nordic Hamstring Exercises" Vs. "Eccentric Exercises" Protocols on Hamstring Strength in Amateur Soccer Players Universitary.; [Diferencias en Los Efectos de Los Entrenamientos de “Curl Nórdico” V/S “Ejercicios Excéntricos” en la Fuerza de la Musculatura Isquiosural en Futbolistas Amateur Universitarios.] - Retamal-Espinoza, M; Arriagada-Tarifeno, D; Cancino-Jimenez, J; Cifuentes-Silva, E (Federacion Espanola de Docentes de Educacion Fisica, 2025)
Introduction: Hamstring injuries have a high incidence in sports, so prevention through training is imperative. The effectiveness of different exercises is constantly sought and evaluated; especially eccentric exercises due to their protective effect. Objective: Compare and observe differences in Work and Peak Torque in the representation of Hamstring strength, through isokinetic dynamometry pre and post execution of eccentric training programs. Methodology: 2 groups of random training, both of which undergo isokinetic evaluation for hamstrings, at speeds of 60°/s and 180°/s bilaterally; Subsequently, a 6-week training was carried out; Group 1 (G1) performed a “Nordic Curl” (CN) training, and Group 2 (G2) an eccentric program (EE) excluding the CN, after the program they were re-evaluated. Results: Both training sessions showed significant differences (p<0.05) in average eccentric strength gain, but not in maximum repetitions (p>0.05). On the other hand, both trainings show large effect sizes. There were no significant differences between the workouts when comparing them in strength gain. Conclusion: The Nordic curl training program (G1) and eccentric exercises that exclude the CN (G2) have proven to be a viable option to generate neuromuscular adaptations that translate into eccentric strength gain and reduction in the risk of injury, thanks to the Optimization of functional ratios. © 2025 Federacion Espanola de Docentes de Educacion Fisica. All rights reserved.